Sludge-based baking-free brick prepared by sewage sludge with high moisture content: Influence of process parameters and environmental risk assessment. Issue 6 (December 2022) - Gao, Hongyu; Zhou, Kai; Su, Di; Zhang, Biwu; Cheng, Fangqin
Abstract: The high-water content and difficult dehydration of sewage sludge are the main factors restricting its disposal and application in China. In the paper, the sludge-based baking-free brick (SBFB) was made from sludge and fly ash - carbide slag - desulfurization gypsum with a certain amount of aggregate using compaction forming technology. The influence of process parameters (e.g., sludge content, aggregate content, molding pressure, curing method and curing temperature) on the properties of SBFB were investigated. Additionally, the environmental risk assessment of heavy metals and organic pollution of SBFB samples were carried out. The results indicated that when the sludge content was less than 30 %, the SBFB strength reaches 13.7 MPa under wet-heat cycle curing, which can meet the national standard of nonbearing wall for building bricks. According to the analysis of SEM and XRD, mullite and silicalite crystals were needle-like structures, which made the sludge particles closely linked with solid waste and compact structure. The appearance of these crystal structures was the internal driving force for the later strength of SBFB. Values of risk assessment criteria decreased through solidification treatment, in which Cd decreased to no risk, As, Pb, Zn decreased to low risk, Cu, Ni had moderate risk. All heavy metals were within China standards (GB5085.3–2007). Compared with sludge, the degradability of protein under curing conditions was greater than 77.35 % because of the decomposition of proteins in gel reaction system. Graphical Abstract: ga1 Highlights: SBFB is made from sewage sludge and solid wastes using compaction forming technology. Wet-heat cycle curing was taken for the maximum content of raw sludge in SBFB. Mullite and silicate were internal driving force for the later strength of SBFB. RAC values decreased through solidification treatment.